Eficacia de un programa educativo sobre información educación y comunicación a trabajadores asistenciales en la mejora del nivel de satisfacción de pacientes sometidos a cirugía mayor ambulatoria - Alvarez Baglietto, Carlos Federico (2011)
Objective: to determine the change of Satisfaction´s level of the patients who underwent Ambulatory Major Surgery by the application of an Educative Program of Information, Education and Communication to a healthcare workers. Design: prospective, longitudinal, pre test- post test with an intervention Setting: Lazarte hospital. Population: 100 health workers and 100 patients attended at the Ambulatory Major Surgical unit, between November 2009 and January 2010 Measurement: data of the test pre intervention compared with post intervention test, to value the Degree of Satisfaction of the patient and the level of Knowledge, Attitudes and Conducts of the healthcare workers through an Information, Education and Communication model. Results: the satisfaction´s level of patients before and after the Program was 69%-10% for the lower Level, 30-38% for the medium Level and 1-52 % for the higher Level. The Knowledge´s level in workers before and after was 92% - 0% for the poor level, 8%-50% for the regular Level and 0%-50% for the good Level. In Attitudes and Conduct´s level in workers before and after was 70%-2% for the inadequate Level, 30%-42% for adequate nor inadequate Level and 0%-56% for the suitable Level. Conclusions: The level of Information, Education and Communication to a healthcare worker’s improves after the application of an Educative Program and as a consequence significantly improves the Degree of patient´s satisfaction.